EVALUATING THE EFFECTIVENESS OF A NUTRITIONAL INTERVENTION ON CHILD DIETARY DIVERSITY AND NUTRITIONAL STATUS IN RURAL ANGUL, ODISHA - ANWESA SAHOO,; DR. HARAPRIYA SAMANTARAYA, (The Journal of Research ANGRAU, 2025)
This study assessed the effectiveness of a three-month nutritional intervention on dietary  diversity and nutritional status among 300 under-five children in rural Angul district, Odisha, covering the period between 2023-2024. The intervention led to a significant increase in dietary diversity scores, from 45.0% to 55.0% for achieving a dietary diversity score (DDS) of 4 (p= 0.032), and notable improvements in nutrient intake: energy (+4.84%, p = 0.045), protein (+12.15%, p = 0.032), and vitamin C (+22.22%, p = 0.015). Anthropometric measurements also showed significant changes, with weight increasing by 6.67% (p = 0.038) and mid-upper arm circumference (MUAC) improving by 7.88% (p = 0.046). Chi-square analysis revealed reductions in underweight (from 35.0% to 25.0%, ² = 8.00, p = 0.005), stunting (from 40.0% to 30.0%, 6.50, p = 0.010), and wasting (from 30.0% to 20.0%, ² = ² = 7.00, p = 0.008). Pearson correlations indicated a positive relationship between dietary diversity and weight (r = 0.45, p = 0.001), height (r = 0.30, p = 0.015), and MUAC (r = 0.40, p = 0.005). Multiple regression analysis identified significant predictors of improved nutritional status, particularly protein ( = 0.25, p < 0.001) and calcium intake ( = 0.20, p = 0.001). ANOVA confirmed significant differences in nutritional status improvement across groups (F = 6.75, p = 0.003). These findings highlight the intervention’s effectiveness in improving child health outcomes and support the implementation of similar programs in comparable settings.